2007
DOI: 10.1128/iai.01357-06
|View full text |Cite
|
Sign up to set email alerts
|

A Live Salmonella enterica Serovar Enteritidis Vaccine Allows Serological Differentiation between Vaccinated and Infected Animals

Abstract: Three precisely defined deletion mutants of Salmonella enterica serovar Enteritidis were constructed, a guanine auxotrophic ⌬guaB mutant, a nonflagellated ⌬fliC mutant, and an auxotrophic and nonflagellated ⌬guaB ⌬fliC double mutant. All three mutants were less invasive than the wild-type strain in primary chicken cecal epithelial cells and the human epithelial cell line T84 and less efficiently internalized in the chicken macrophage cell line HD11. The ⌬fliC mutant was pathogenic in orally infected BALB/c mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 49 publications
(46 reference statements)
1
17
0
Order By: Relevance
“…Our results are in harmony with the in vitro invasion results of previous publications comparing wild-type strains and nonflagellated (fliC-deleted) mutants of different Salmonella serovars, indicating that flagellae are necessary for the proper invasion of S. Enteritidis into human Caco-2 and Hep-2 tumour cells (Van Asten et al, 2000;La Ragione et al, 2003), but differ somewhat from those obtained on fliC-deleted mutants of different strains of S. Enteritidis (Adriaensen et al, 2007;Methner et al, 2011b). Adriaensen et al (2007) found that the fliCΔ mutant of their wild-type S. Enteritidis 76Sa88 showed less reduced invasion of human (T84) or chicken intestinal epithelial cells. Unfortunately, these authors did not compare their double-deletion mutant (ΔguaB ΔfliC) in day-old chicks to either the ΔfliC single mutant or to the wild parent strain.…”
Section: Inhibition (%)supporting
confidence: 80%
See 4 more Smart Citations
“…Our results are in harmony with the in vitro invasion results of previous publications comparing wild-type strains and nonflagellated (fliC-deleted) mutants of different Salmonella serovars, indicating that flagellae are necessary for the proper invasion of S. Enteritidis into human Caco-2 and Hep-2 tumour cells (Van Asten et al, 2000;La Ragione et al, 2003), but differ somewhat from those obtained on fliC-deleted mutants of different strains of S. Enteritidis (Adriaensen et al, 2007;Methner et al, 2011b). Adriaensen et al (2007) found that the fliCΔ mutant of their wild-type S. Enteritidis 76Sa88 showed less reduced invasion of human (T84) or chicken intestinal epithelial cells. Unfortunately, these authors did not compare their double-deletion mutant (ΔguaB ΔfliC) in day-old chicks to either the ΔfliC single mutant or to the wild parent strain.…”
Section: Inhibition (%)supporting
confidence: 80%
“…The most straightforward solution to provide a negative serological marker for a Salmonella strain is the elimination of flagellae. A nonflagellated S. Enteritidis vaccine candidate strain (ΔguaB, ΔfliC) has been produced and proven to be promising in the protection of chicks against homologous challenge (Adriaensen et al, 2007). Further fliC-S. Enteritidis vaccine candidates have been reported by Methner et al (2011a) and Matulova et al…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations